(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Alternating hemiplegia of childhood (AHC) is a rare neurodevelopmental disorder characterized by recurrent attacks of hemiplegia affecting either side of the body, oculomotor and autonomic disturbances, movement disorders, and progressive cognitive impairment. Herein we reported a case who presented with developmental delay, abnormal eye movement, dystonic attack, episodes of alternating hemiplegia, and multifocal seizures. Investigations performed including, MRA of the brain, EEG as well as metabolic evaluation, were normal. A genetic study revealed a mutation in the ATP1A3 gene (c.2878G>A) associated with AHC-2. Based on history, examination, and genetic study, a diagnosis of Alternating hemiplegia of childhood was ascertained. Journal of National Institute of Neurosciences Bangladesh, January 2024;10(1):70-74